1000 words stem - Pottle, Jules; Hare, Rachael; Moul, Robin; Parkes, Sophie; Thomas, Sadie (London Dorling Kindersley limited, 2023)
"Did you know that science is all around us, even on the playground? Open the pages of this illustrated picture and word book for young readers to discover the wonders of STEM in 1000 words.This fascinating STEM education book for kids is packed with bright, detailed illustrations and easy-to-read terms. Every picture-packed page is full of scientific concepts such as sound, light, senses, and machines, with words for each image
Arts (sports)
Keywords: Science; Science and Maths General; Sciences Ouvrages pour la jeunesse